1993
DOI: 10.1159/000236563
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Acute Experimental Allergic Encephalomyelitis by the Synthetic Sex Hormone 17-Alpha-Ethinylestradiol: An Immunological Study in the Lewis Rat

Abstract: Induction of experimental allergic encephalomyelitis (EAE) in female Lewis rats led to the well-known clinical symptoms and histological signs. Treatment with the synthetic estrogen 17-α-ethinylestradiol (EE) from day ––4 before induction until day 21 after induction resulted in partial suppression of these signs and symptoms. Analysis of the peripheral blood leukocyte (sub)populations in these treated animals indicated some remarkable changes. However, these changes were also observed without EE treatment. EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 16 publications
2
33
1
2
Order By: Relevance
“…Our study differs from previously published studies that reported treatment with estrogen at levels equivalent to or exceeding pregnancy levels suppress the development of EAE (24,25,30), and that the primary mechanisms by which this occurs is through immune deviation toward Th2 cytokines (15,37,38). It is quite possible that the dose and form of estrogen has a critical role in determining the mechanisms of disease inhibition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study differs from previously published studies that reported treatment with estrogen at levels equivalent to or exceeding pregnancy levels suppress the development of EAE (24,25,30), and that the primary mechanisms by which this occurs is through immune deviation toward Th2 cytokines (15,37,38). It is quite possible that the dose and form of estrogen has a critical role in determining the mechanisms of disease inhibition.…”
Section: Discussioncontrasting
confidence: 99%
“…Pregnancy has been shown to suppress the development of EAE (22,23), and estrogen administered at levels equal to or greater than those in pregnancy have been shown to diminish clinical disease (24,25). In recent studies from our laboratory, ovariectomy and loss of endogenous estrogen enhanced the severity of EAE, whereas treatment of mice with estrous and diestrous levels of exogenous estrogen effectively suppressed EAE (26,27).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 97%
“…In this study we demonstrate that EE, an orally active estrogen compound found in oral contraceptives, protects against the development of EAE when administered at the time of disease induction, similar to E2. This oral suppression protocol was even more effective than daily s.c. injections of EE given to Lewis rats during disease induction, as reported by Trooster et al (20). A previous study by Kim et al (16) demonstrated that estriol, given as a pellet after the onset of clinical signs, could reduce the severity of EAE in mice.…”
Section: Discussionmentioning
confidence: 68%
“…However, structural differences preclude detection of EE using Abs to E2. Earlier studies involving s.c. treatment with EE in rats demonstrated partial suppression of EAE (20,21). However, no significant differences in blood leukocyte populations were found between treated and untreated animals (20).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 78%
See 1 more Smart Citation